The Wrath of God in Revelation - Michael R. Burgos (Jurnal Ilmiah Tafsir Alkitab, 2026)
The book of Revelation presents a vivid and multifaceted depiction of the wrath of God that is both distinctive and harmonious with its occurrences throughout the Old Testament and the remainder of the New Testament. This study offers an exegetical analysis of the passages in Revelation that explicitly reference divine wrath, emphasizing its eschatological finality and irrevocable character as executed by the Father and the risen Lamb upon all who persist in rebellion. A comparative examination with canonical portrayals reveals Revelation’s heightened apocalyptic imagery, such as the wine of God’s wrath, the winepress of his fury, and the bowls of judgment, while affirming continuity with Old Testament types of historical and prophetic judgment. Additionally, divine wrath is briefly considered as a genuine expression of God’s perfect emotional life in response to evil, consistent with the doctrine of divine impassibility. The study concludes with a consideration of Revelation’s presentation of final punishment as eternal conscious torment.